Pemberian POC Urine Ternak Berbeda Konsentrasi Terhadap Pertumbuhan dan Serapan Kalium Tanaman Jagung Manis (Zea Mays L.) - Dinata, Dhanu Pangestu Anggi; Sholihah, Anis (Folium : Jurnal Ilmu Pertanian, 2024)
Livestock urine is one of the potential raw materials for for making potential liquid organic fertilizer (POC). Livestock urine contains various important nutrients, such as nitrogen, phosphorus, and potassium. Research This research was conducted to obtain the right and efficient concentration of rabbit urine liquid organic fertilizer on growth and K uptake. Concentration of rabbit urine liquid organic fertilizer that is appropriate and efficient on the growth and K uptake of sweet corn plants. This research was organized using a completely randomized design (RAL) consisting of 5 levels, namely K0 (no urine), K1 (POC concentration of 5%), K2 (POC concentration 10%), K3 (POC concentration 15%), and K4 (20% concentration). Data from the observations obtained The data from the observations obtained were analyzed using variance analysis (ANOVA) or F test at the 5% level to determine the effect of POC treatment along with the concentration of urine. If there is significant differences, it was continued with the Least Significant Difference (BNT) test with a level of 5%. Simple linear regression analysis was also conducted simple linear regression analysis to determine the optimum concentration on sweet corn plant growth. The results of the study generally showed that the K4 treatment (20% POC concentration) is the best treatment and significantly influenced the parameters of plant height, stem diameter, number of leaves, and K uptake in sweet corn plants. Based on simple linear regression test simple linear regression test can not be determine the optimum dose, because it still shows a simple linear response, meaning that with increasing concentrations, the uptake of K in sweet corn plants is higher.